Alone eaudiobook - Gardner, Lisa (Detective D.D. Warren, 2005)
“Like all the best suspense novels,  Alone  will leave you shaken. . . . You can't wait to see what happens next.”— People   Who can you turn to when you’re at your most vulnerable? State Trooper Bobby Dodge watches a tense hostage standoff through the scope of his sniper rifle.  Dodge has only one second to react, or a woman and her child may die. Where can you hide when this killer comes? The woman at the other end of Bobby Dodge’s rifle isn’t only in trouble—she is trouble.  Cool, beautiful, and dangerously sexy, Catherine Rose Gagnon’s life will change in an instant of violence. It’s the most terrifying place to be. . . .  When Bobby pulls the trigger, someone will die.  And then no one will be above suspicion, no one beyond harm.  And no one will see death coming until it has them cornered, helpless, and alone .